FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI DALAM ALIH KOMODITI KOPI (Coffee sp) KE KAKAO (Theobrroma cacao L. ) DI DESA TERTAP KECAMATAN JARAI KABUPATEN LAHAT SUMATERA SELATAN - M. Agus Maryanto; Musriyadi Nabiu; Septri Widiono (Jurnal Agrisep)
This study aims to understand the process, reasons for the actions of farmers and analyze the factors that influence farmers to switch commodities. The number of respondents is 46 farmers selected using Simple Random Sampling. Description and multiple regression are used in this research. The results showed that the commodities convertion is done in some stages. The main reason is that farmers are able to earn income from their initial plants while they wait their new crops starting to produce. There are three reasons that farmers switch of social, economic, and agronomists. Social reasons, namely, to see the success of a friend of 41.30%, follow friends 39.13%, and their-owned beliefs 26.08%. Economic reasons is the high price of cocoa 60.86%, continuity of production 100% and marketing easy in 93.47%. Agronomic reasons, namely cocoa seedlings are easy to get 95.65%, maintenance / cultivation is easy 89.13%, and easy in post- harvest handling 93.47%. The results of regression analysis showed the number of dependents, a price comparison index, previous farm receipts, the coffee plant age, perception of control of the commodity, ease of cultivation and post harvest simultaneously significantly affect the percentage of land area converted. While the partial factors of coffee plant age and the perception of the commodity rather have real impact on the land area converted commodities.